Tunable thermal, flame retardant and toxic effluent suppression properties of polystyrene based on alternating graphitic carbon nitride and multi-walled carbon nanotubes. Issue 33 (7th September 2015) - Shi, Yongqian; Long, Ze; Yu, Bin; Zhou, Keqing; Gui, Zhou; Yuen, Richard K. K.; Hu, Yuan
<x xml:space="preserve">Abstract</x> Significant improvements in thermal and flame retardant properties of polymeric materials at low loadings hold tremendous promise for fire safety materials.